Analysis of debt settlement mechanisms to third party providers of goods and services at the District Government providing goods and services - Mohammad Rizki Aditya; Mujahid; Abdul Samad A (Universitas Muhammadiyah Palu, 2025)
This research aims to analyze the debt settlement mechanism to third party providers of goods and services as well as the supporting and inhibiting factors of the debt settlement mechanism to third party providers of goods and services. The approach that researchers used in this research was a qualitative approach with a descriptive research strategy. This research was carried out at the North Penajam Paser Regency Government from February to March 2025. The informants in this research were 5 (five) informants. The results of this research show that the mechanism that works in resolving debts from third parties providing goods and services is the process of proposing debt recognition from Regional Work Units, reconciling debt data, and carrying out debt reviews as debt recognition which will be budgeted for in the Amendment to the Regional Revenue and Expenditure Budget. In addition, the Review Results Report becomes a reference for the Regional Financial and Asset Agency to record in the Regional Government Financial Report. Debt settlement will be carried out if the work package owed has been stated and included in the sub-activities in the Amendment to the Regional Revenue and Expenditure Budget for the following year. The supporting factor in resolving debts to third party providers of goods and services is the existence of the Minutes of Debt Reconciliation as an initial reference in the process of resolving debts to third party providers of goods and services, while the inhibiting factor is the absence of regulations in the North Penajam Paser Regency Government at the level of regional head regulations that regulate debt management and the commitment of third parties together with regional work units in terms of completing the required documents for debt settlement.